Cellular Senescence in the Development and Treatment of Cancer - Saretzki, Gabriele (Current Pharmaceutical Design, 2010)
Senescence is defined as an irreversible growth arrest that is characterised by a changed morphology, gene expression pattern and chromatin structure as well as an activated DNA damage response. Senescence has a dual role for tumour development. Firstly, it acts as a tumour suppressor to prevent the proliferation of seriously damaged cells. Important mechanisms ensuring the stop of genomically altered cells to proliferate are the activation of ATM, p53 and the DNA damage response (DDR). In addition it emerges in recent years that oncogene activation acts as a genetic stress and induces senescence as well using similar downstream components: DNA damage activation, changes in gene expression and chromatin structure. Therefore, senescence functions as a powerful tumour suppressor that protects cells expressing activated oncogenes in vivo from becoming neoplastic and malignant. The fact, that oncogene induced senescent cells were mainly found in early, pre-malignant tumour stages suggest that this senescent state has to be overcome during tumourigenesis in order for a tumour to progress to malignancy. At the same time cellular senescence is increasingly recognised as a possible outcome for the treatment of human tumours because it is executed by cells in response to therapeutic treatments, such as drugs and irradiation. While historically apoptosis was considered the only desirable outcome of any anti-neoplastic treatment it emerges recently that senescence could be a potential alternative outcome for tumour therapy in vivo. Animal and tissue culture models have been developed over the last years shedding more light on this novel field of cancer treatment. Whether senescence induction is an advantage or a backdrop for tumour treatment has still to be elucidated since experimental proof in human tumour models is still in an infant stage. This review focuses on the basic mechanisms and recent advances for the induction of senescence as a potential outcome of cancer therapy and discusses the potential for a clinical application.
Keywords: tumour therapy